Heart failure - Gardner, Roy S.; McDonagh, Theresa A.; Walker, Nicola L. ([Oxford] : Oxford University Press, 2014)
Heart failure is a common and potentially lethal condition. It is the only cardiovascular disease that is increasing in both incidence and prevalence. This book is a practical and comprehensive manual aimed at the team of professionals caring for patients with heart failure.
This edition previously issued in print: 2014.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 23, 2016).
Keywords: Heart failure